ASPHALT-BOUND MASONRY BLOCK INCORPORATING CONSTRUCTION DEMOLITION WASTE - I Nyoman Arya Thanaya (Journal of Civil Engineering, 2009)
Utilization of waste aggregates for construction industry had been encouraged in line with increasing pressures to reduce exploration of natural aggregates. One alternative material that can be used as masonry block unit is the construction demolition waste (CDW) with asphalt as the binder (CDW block). The objective of this paper is to produce CDW block with a performance equal to the concrete block commonly used in the United Kingdom with a compressive strength between 3.5 MPa and 7 MPa and the specific creep strain less than 100 microstrain. The CDW block requires suitable particle size proportion, in order to obtain satisfactory results and to meet the demand of using minimum bitumen content and low compaction level. The CDW block requires sufficient heat curing to harden the asphalt. It was found that CDW materials were a very suitable material to be used for making CDW blocks. Compaction level of 2 MPa and curing regime of 200°C for 24 hours were sufficient and gave satisfactory results.